THE INFLUENCE OF SHOPPING LIFESTYLE AND FLASH SALES ON IMPULSIVE BUYING BEHAVIOR AT SHOPEE E-COMMERCE FOR GENERATION Z IN EAST LUWU REGENCY - Madania, Sarah Putri; Purwanto, Sugeng (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The purpose of this study was to determine the effect of shopping lifestyle and Flash Sales on impulsive buying behavior in shopee E-commerce for Generation Z in East Luwu Regency. This study uses quantitative research methods. The population studied was Shopee E-commerce users in East Luwu Regency, a sample of 108 people and the sampling technique used was a non-probability technique using purposive sampling. The data analysis technique uses the component-based Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) analysis tool. The results showed that a shopping lifestyle has a positive and significant effect on impulsive buying and Flash Sales have a positive and significant effect on impulsive buying